The Influence of Impulsivity and Values on Impulsive Buying - Katarina Sokić; Darija Korkut (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
This study examined the influence of impulsivity and values orientations on impulsive buying tendencies on convenience sample from the City of Zagreb (N = 220, 56% women) using the Baratt impulsivity scale, Buying Impulsivity Scale, and Value Orientation Scale. Participants were between the ages 20 years and 55 years, and all were employed. As predicted, bivariate correlations showed that impulsive buying tendencies were positively related to attention, motor and non-planning impulsivity. In addition, the results revealed positive association between impulsive buying tendencies and hedonistic value orientation. Results of hierarchical regressions analyses showed that motor and non-planning impulsivity, but not attention impulsivity, positively predicted impulsive buying tendencies. Moreover, the multiple regression analysis has shown that impulsivity and values explained 35% of the variance in impulsive buying tendencies. The results are in line with the theoretical assumptions proposed that some aspects of impulsive behaviour are associated with utilitarian-hedonistic value orientation.
Keywords: A13; D12; D87; D91; 330; impulsivity; value orientations; impulsive buying